Effect of purple corn extract on performance, antioxidant activity, egg quality, egg amino acid, and fatty acid profiles of laying hen - Li, Jiaxuan; Zhou, Di; Li, Hui; Luo, Qingyuan; Wang, Xu; Qin, Jixiao; Xu, Yiqing; Lu, Qi; Tian, Xingzhou (Frontiers in Veterinary Science, 2023)
The objective of this study was to investigate the effects of anthocyanin-rich purple corn extract (PCE) on performance, antioxidant potential, egg quality, egg amino acid and fatty acid profiles of laying hens during the late laying period. A total of 360 88-wk-old laying hens were randomly divided into 4 groups, and fed a basal diet (CON) or a basal diet supplemented with 120 (LP), 240 (MP), and 360 mg/kg (HP) PCE, respectively. No significant difference (P > 0.05) was observed in the ADFI or average egg weight among the groups. However, the mean feed to egg ratio was quadratically decreased (P < 0.05) in the LP and HP treatments. The mean TAC was linearly and quadratically increased (P < 0.05) in all PCE supplemented treatments. The mean SOD was linearly and quadratically increased (P < 0.05) in the HP treatment compared with CON and MP groups. The GPX was linearly and quadratically lower in the HP treatment compared to the CON and LP groups. Differently, the MDA was linearly and quadratically lower (P < 0.05) in the PCE treatments compared with the CON. The eggshell thickness value in MP and HP treatments were linearly and quadratically higher (P < 0.05) than that of the CON and LP groups. Hens fed PCE was linearly and quadratically increased (P < 0.05) most individual amino acids, essential amino acid and umami amino acid profiles in egg. The PCE treatments showed linearly and quadratic (P < 0.05) effect on the myristoleate, heptadecenoic acid, elaidic acid, eicosenoic acid, heneicosanoic acid, and eicosatrienoic acid concentrations. Moreover, dietary supplementation of PCE was quadratically increased egg stearic acid, oleic acid, arachidic acid, linolenic acid methyl ester, arachidonic acid, diphenylamine, docosahexaenoic acid, monounsaturated fatty acid, and polyunsaturated fatty acid compared to the CON. Therefore, dietary anthocyanin-rich PCE can enhance plasma antioxidant potential, beneficial to egg production, and improves amino acids and fatty acids in hen eggs during the late laying period.